Efektifitas Penerapan Program Penanganan Turnover Karyawan Staf Manajemen PT. BEHAESTEX Group - Ratna Juita (University of Darussalam Gontor, 2015)
The purpose of this research are to recognize turnover management program implementation effectiveness of management staffs of PT. BEHAESTEX Group and know the causes aspect the employee who leave out then program that given is the target precise. This research used qualitative method with qualitative descriptive research type. Information digging by in depth interview, observation, and documentation taken from HRD data. Research subjects as 18 respondents obtained from staff employee who already terminated from PT. BEHAESTEX Group since 2010 until 2012 and represented each department. The result of the research indicates that effective turnover management program only one program that is employee training. While three other programs that are induction and orientation, coaching and counseling, building and brainstorming ineffective. The causes are the aim does not appropriate, human resources development qualification as program implementer is lack of competence and inconsistency program implementation. Beside found that the causes aspect which result employee terminated could be classified with work term under two years namely unable to adjustment with corporate culture, high idealism and accepted as civil servant. While work term over two years the causes are injustice pay, superior mind pattern still departmental and career stage is unobvious.